Molecular typing of Salmonella weltevreden and Salmonella chincol by pulsed-field gel electrophoresis (PFGE) and enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) - Sahilah, A.M.; Son, R.; Rusul, G.; Samuel, L.; Hassan, Z.; Lum, K.Y.; Ahmad, M.A. (Kluwer Academic Publishers., 2000)
Genomic DNA of Salmonella weltevreden (10 isolates from poultry, two isolates each from raw vegetables and river water) and S. chincol (15 isolates from poultry) were characterized by pulsed-field gel electrophoresis (PFGE) and enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) analysis. These isolates originated from a single location in Kajang, Selangor. The results of the PFGE and ERIC-PCR were analysed and comparisons were made using GelCompar software. ERIC-PCR with primers ERIC1R and ERIC2 discriminated the S. weltevreden into five clusters and two single isolates and S. chincol into two clusters and two single isolates at a similarity level of 80%, respectively. PFGE produced a single cluster and eight single isolates for S. weltevreden, and one cluster and 11 single isolates for S. chincol at a similarity level of 80% after digestion with the restriction enzyme XbaI, respectively. These results demonstrate that both PFGE and ERIC-PCR are suitable tools for molecular typing of the isolates examined.